2022
DOI: 10.3389/fmolb.2022.851547
|View full text |Cite
|
Sign up to set email alerts
|

Predictive functional, statistical and structural analysis of CSNK2A1 and CSNK2B variants linked to neurodevelopmental diseases

Abstract: Okur-Chung Neurodevelopmental Syndrome (OCNDS) and Poirier-Bienvenu Neurodevelopmental Syndrome (POBINDS) were recently identified as rare neurodevelopmental disorders. OCNDS and POBINDS are associated with heterozygous mutations in the CSNK2A1 and CSNK2B genes which encode CK2α, a serine/threonine protein kinase, and CK2β, a regulatory protein, respectively, which together can form a tetrameric enzyme called protein kinase CK2. A challenge in OCNDS and POBINDS is to understand the genetic basis of these disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 155 publications
1
8
0
Order By: Relevance
“…Our data provide in silico and functional evidence indicating that the CSNK2B mutations, p.Leu39Arg and p.Met132LeufsTer110, identified in two POBINDS patients, behave as LoF, which has also also been predicted for CSNK2B variants, resulting in a premature stop codon (PTC) [11,13,34,41]. This is suggestive of the haploinsufficiency of CK2beta as a common pathogenetic mechanism in POBINDS.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our data provide in silico and functional evidence indicating that the CSNK2B mutations, p.Leu39Arg and p.Met132LeufsTer110, identified in two POBINDS patients, behave as LoF, which has also also been predicted for CSNK2B variants, resulting in a premature stop codon (PTC) [11,13,34,41]. This is suggestive of the haploinsufficiency of CK2beta as a common pathogenetic mechanism in POBINDS.…”
Section: Discussionsupporting
confidence: 61%
“…Patient 1 had a missense mutation affecting the very conserved Leucine 39 in the KEN box-like motif (aa [32][33][34][35][36][37][38][39][40] in the N-terminal segment of the CK2beta (p.Leu39Arg). Notably, 30% of the published patients with the CSNK2B missense mutation and either POBINDS or IDCS presented with a recurrent or unique mutation, which significantly clustered in this short motif (Figure 11A) [12,28,[34][35][36][37][38][39][40][41]. The MetaDome web tool [42], which used to interpret the significance of CSNK2B mutations in the tolerance landscape of the gene, indicated that the five variants were located in a region of high intolerance (low missense over synonymous variant count ratio) (Figure 11B).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the disruption of this loop is expected to exert the most deleterious effects on the brain and other organs, relative to disruptions in other protein-coding regions of CK2α (Wu et al ., 2021). Most of the truncating variants (nonsense and frameshift) likely result in the complete loss of normal protein folding (Unni et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, missense mutations of CSNK2A1 (casein kinase 2 alpha 1) in the deleted region have been recently identified as the cause of an autosomal dominant Okur-Chung neurodevelopmental syndrome (OCNDS; OMIN #617062). CSNK2A1 encodes a kinase protein casein kinase II (CK2α) (Unni et al, 2022). CK2α is a highly conserved serine-threonine kinase involved in various cellular processes, including cell cycle control, apoptosis, embryonic development, and circadian rhythms (Dominguez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%